Dynamic modeling of rotor-bearing-housing system with local defect on ball bearing using mass distribution and energy methods. (September 2021) - Liu, Yaofeng; Yan, Changfeng; Wang, Kai; Gao, Xianghong; Zhang, Xin; Wu, Lixiao
The rotor-bearing-housing system is widely used in rotating machines, which influences the performance of the whole machine. Considering the distribution of rotor mass, the rotor-bearing-housing system with local defect in the outer ring is modeled based on the energy method. In order to make the model agree well with the experimental results, a new rotor mass distribution method was introduced in the modeling process. The simulated vibration signal was obtained by solving the dynamic equations with the Runge-Kutta method. The vibration responses of rotor-bearing-housing system under different distributed disks at both drive end and fan end are simulated. In the simulation results, the outer ring fault signal at the drive end and the vibration signal at the fan end are compared with the experimental signals to discuss the influence of rotor mass distribution on the vibration response of the bearing at both ends of the system. The results show that the simulation signal generated by the dynamic model of the rotor-bearing-housing system with a more uniform rotor mass distribution is more consistent with the experimental signal. The vibration response of the faulty bearing at drive end is compared at different defect sizes, and the variation trend of the amplitude of their characteristic frequency is obtained. This method is helpful for structural optimization and fault diagnosis of the rotor-bearing-housing system.